Contribution of Teacher Performance, Socio-Economic Status, and Physical Activity to the Body Mass Index of Student in Semarang Tengah (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Pandemic, it affects the learning process, especially in physical education (PE) class. This study aims to find the contribution of PE teacher performance, family socioeconomic status and physical activity during the pandemic to the body mass index of elementary school students. Respondents consisted of 436 students and 16 teachers of civil servants, non-civil servants, and foundations spread across 12 public and private schools in the district of Central Semarang. The data were analyzed using multiple regression method with the help of SPSS 25 to find the value of the correlation coefficient and the coefficient of determination. With the results 1) Significant relationship between the performance of PE teachers and physical activity on the body mass index of students with a low contribution of 31%. 2) A significant relationship between the performance of PE teachers and socioeconomic status on the body mass index of students with a moderate contribution of 47% . 3) There is a significant relationship between physical activity and socioeconomic status on the body mass index of students with a moderate contribution of 42.2%. 4) There is a significant relationship between the performance of PE teachers, physical activity and socioeconomic status on the body mass index of students with a moderate contribution of 47.4%. The conclusion is that simultaneously the performance of PE teachers, children's physical activity during the pandemic and the socioeconomic status of the family have a significant relationship with a moderate contribution.